Temporal variations in coda attenuation associated with the 2008 Wenchuan (MW7.9) Earthquake in SW, China - Junhua Hu (KeAi Communications Co., Ltd., 2021)
In this study, waveform data obtained from Western Sichuan Seismic Array (WSSA) in China was utilized to reveal the temporal variations in coda attenuation around the eastern Tibet Plateau and Western Sichuan. Based on the single-scattering model, coda attenuation factor Qc−1 is calculated in narrower overlapping frequency bands at 1.0–24 Hz by measuring the coda decay rates for local earthquakes before and after the Wenchuan mainshock. The temporal variations in coda attenuation are investigated within three periods. The period I lasted from January 2007 to the end of 2007. The period II lasted from January 2008 till Wenchuan earthquake. The period III lasted from the mainshock to the end of 2008. The resulted temporal variations demonstrate an increase in average Qc−1 by approximately 35%–45% in the vicinity of Longmenshan and 30%–35% in Sichuan Basin after the Wenchuan earthquake in lower frequency bands within 1.25–8 Hz. On the contrary, the average Qc−1 is shown to decrease by approximately 10%–18% in southern segment of Longmenshan, 15%–38% in the Chuan-Dian block, and 10–12% in the South China block. These results are confirmed by a statistical t-test at 99.9% confidence level. No statistically significant change in Qc−1 (<10%) is found in the Songpan-Ganzi block after the mainshock. Temporal variations of coda attenuation differ significantly in individual blocks after the mainshock. The coda attenuation is proposed to be a beacon to tectonic static stress changes associated with the Wenchuan earthquake.